The influence of taxpayer awareness level, tax knowledge, income level and sanctions on motor vehicle tax compliance in Yogyakarta city - Nurul Hafizhah; Fajar Satriya Segarawasesa (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyze the influence of taxpayer awareness, tax knowledge, income level, and tax sanctions on motor vehicle taxpayer compliance in Yogyakarta City. The method used in this study is a quantitative research method. The type of research data that will be used in this study is the type of primary data collected by researchers and obtained from the results of questionnaires by respondents. The population in this study were all taxpayer vehicles registered at the Yogyakarta City SAMSAT. The data analysis method used in this study is a multiple linear regression test with a classical assumption test before the regression test is carried out. The purpose of this Classical Assumption test is carried out so that the regression model is ideal (unbiased), so it is necessary to conduct an examination using the Normality Test, Heteroscedasticity and Multicollinearity Test.